Transcriptome Sequencing-Based Mining of Genes Associated With Pubertal Initiation in Dolang Sheep - Zhang, Zhishuai; Sui, Zhiyuan; Zhang, Jihu; Li, Qingjin; Zhang, Yongjie; Xing, Feng (Frontiers in Genetics, 2022)
Improving the fertility of sheep is one of the important goals of goat breeding as it greatly increases productivity. The Dolang sheep is a typical representative of the excellent flavor of lamb in Xinjiang and is also the main local sheep breed and meat source in the region. To explore the genes associated with the initiation of puberty in Dolang sheep, the hypothalamic tissues of Dolang sheep prepubertal, pubertal and postpubertal periods were used as samples for RNA-seq analysis on Illumina platform in this study. 64.08 Gb Clean Data were generated. 575, 166 and 648 DEGs were detected in prepuberty_vs_puberty, postpuberty_vs_prepuberty and postpuberty_vs_puberty, respectively. Based on Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis, the related genes involved in the initiation of puberty in Dolang sheep were mined. Ten genes that play direct or indirect functions in the initiation process of puberty in Dolang sheep were screened in GO and KEGG results. Additionally, the quantitative real-time PCR was used to verify the reliability of the RNA-Seq data. This study has an important guideline for the selection and breeding of Xinjiang Dolang sheep with short reproductive cycle.